Impact of drying on dissolution behavior of carvedilol-loaded sustained release solid dispersion: development and characterization. Issue 9 (September 2020) - Halder, Shimul; Ahmed, Fairuza; Shuma, Madhabi Lata; Azad, M.A.K.; Kabir, Eva Rahman
Abstract: Purpose: The present study aimed to develop carvedilol (CAR)-loaded (25% w/w) sustained release solid dispersion (SRSD), for enhanced dissolution and to explore the applicability of different industrially accessible drying techniques. Methods: SRSD-CAR containing different ratios of polymers were prepared and physicochemically characterized. Dissolution study was carried out in both sink and supersaturated conditions to identify the possible enhancement in dissolution behavior. Results: Based on the solubility study, Kolliphor® P188 and Eudragit® RSPO (50:25, % w/w) ratio exhibited the highest solubility among the samples and was chosen as the optimal composition of SRSD-CAR for further characterization. The crystallinity assessments of the optimized formulation indicated amorphization of CAR in the formulation, bring about improved solubility of CAR. The infrared spectroscopic study revealed minor transitions; demonstrating the absence of significant interactions between drug and carrier. Furthermore, the SRSD-CAR exhibited immediate formation of nano particles when dispersed in water. Dissolution study revealed significant improvement in dissolution behavior, with a release of CAR in a gradual manner compared to crystalline CAR. From the dissolution kinetics analysis, the Korsmeyer Peppas model fit the best and diffusion was predominant in release of CAR. The drug release pattern showed insignificant differences between the SRSD-CAR formulations prepared by rotary vacuum drying and freeze drying. Conclusion: From these experimental findings, SRSD approach might be a favorable dosage option for CAR, offering improved biopharmaceutical properties. Abstract : Biopharmaceutical; Carvedilol; drying; solubility; sustained release solid dispersion; Pharmaceutical Engineering; Drug Delivery; Drug Development; Pharmaceutical Science; Drug Delivery.